Multifunctional Magnetic Nanoparticles for Dynamic Imaging and Therapy. Issue 11 (15th September 2022) - Ko, Min Jun; Hong, Hyunsik; Choi, Hyunjun; Kang, Heemin; Kim, Dong‐Hyun
Abstract : Multifunctional magnetic nanoparticles (MNPs) exhibit unique properties, such as remote motion controllability, degradability, and diagnostic imaging, which are typically not shown in nonmagnetic nanomaterials. MNPs remotely controllable via magnetic fields offer advantages of high tissue penetrability and biocompatibility. In this review, recent advances of multifunctional MNPs exhibiting unique characteristic for therapeutic applications are summarized, which utilize the "dynamic" motion, iron ion degradation, or imaging‐guided targeting of the MNPs under diverse magnetic field modes. The magnetic field‐controlled MNP motion enables spatiotemporal and reversible in situ cell regulation and mechanosensitive molecule modulation or thermal energy generation. Furthermore, the iron‐based MNPs can produce degraded ions and reactive oxygen species to enable targeted ferroptosis therapy with medical imaging‐guided approaches. The state‐of‐the‐art imaging‐guided "dynamic" therapy using the MNPs that can provide in situ feedback at each therapeutic stage is highlighted. Potential hurdles in translating the magnetic dynamic imaging and therapy toward clinical practices are also discussed. The imaging capability of the MNPs during "dynamic" magneto‐cell regulation enables noninvasive, safe, localized, and on‐demand regulation for the state‐of‐the‐art regenerative therapy, immunotherapy, and cancer treatment. Abstract : Multifunctional magnetic nanoparticles (MNPs) can exhibit unique properties of dynamic motion or degradation or imaging‐guided targeting under magnetic field. In this review, recent progress on simultaneous imaging and dynamic magnetocell regulation utilizing multifunctional MNPs is highlighted, which enables noninvasive, safe, localized, and on‐demand regulation toward tissue engineering, magnetic hyperthermia, ferroptosis, and imaging‐guided therapy.